Immunohistochemical investigation of endometrial leukocytes in implantation period in rats with streptozotosin-induced diabetes - Nacar, Emel; Bozkurt, Yeşim Akaydin; Koç, Ahmet; Nacar, Ahmet (Polish Journal of Pathology, 2016)
Our first aim was to determine the total leukocyte profile in implantation. Second aim was to detect the changes in uterine leukocyte profile in diabetes, a common accompanying disease. For this purpose 4 groups are formed with Wistar albino rats weighing 250-300 g. Two of the groups were non-diabetic and two of them were diabetic. One of the diabetic and one of the non-diabetic groups were left pregnant. Then uterus tissues of pregnant animals were removed in the 5th and 7th days of pregnancy together with tissues of other two non-pregnant groups. Tissues were analyzed immunohistochemically with antibodies CD45, CD3, CD4, CD8, CD56, CD68 and CD79a. It was revealed that pregnancy increased immune staining of CD68, CD3, CD45 and CD56 in endometrium. In addition it was observed that immune staining density of CD68, CD45 and CD56 decreased in diabetes. In the histopathological examination, significant degeneration was detected in the endometrium of diabetic rats. Diabetes could decrease leukocyte proportions in decidua in early pregnancy periods. Therefore immune cell therapies could be administrated in diabetes related problems of pregnancy.